Combined Neuroprotective Strategies Blocked Neurodegeneration and Improved Brain Function in Senescence-Accelerated Mice - Malerba, Helena Nascimento; Pereira, Arthur Antonio Ruiz; Pierrobon, Marcela Favoretto; Abrao, Guilherme Souza; Toricelli, Mariana; Akamine, Eliana Hiromi; Buck, Hudson Sousa; Viel, Tania Araujo (Frontiers in Aging Neuroscience, 2021)
The increase in quality of life combined with drug strategies has been studied as possibilities for improving memory and delaying the onset of neurodegenerative diseases. Previous work published by our group has shown that microdose lithium and the enriched environment can improve memory in both mice and humans. To better elucidate this relationship, this study aimed to evaluate whether the chronic combination of these two strategies could increase healthy aging in Senescence Accelerated Mouse-Prone 8 (SAMP8). Animals were submitted to either one or both of these strategies until the age of 10 months when they were anesthetized and killed, and the hippocampus of each animal was extracted. Untreated SAMP-8 presented worse memory and reduced neuronal density with greater neurodegeneration and increased amyloid-β plaque density than the control group. Moreover, significant alterations in proteins related to long-term potentiation including synaptophysin and BDNF were observed in this group. The strategies used in the study maintained long-term memory, reduced anxiety, and increased neuroprotection. Both strategies were efficient in reduce neurodegeneration and increase parameters related to memory maintenance. In many experiments, the combination of the two strategies was more effective in improving healthy aging. The present work sheds light on the combination of strategies that choose to improve the quality of life and drugs with low side effects. Moreover, it opens perspectives for a new field of study for healthy aging.